THE ASSOCIATION OF DURATION OF TYPE 2 DIABETES MELLITUS WITH THE PREVALENCE OF PERIPHERAL DIABETIC NEUROPATHY - Sabari, Nixie; Mellow, Prettsun Ang; Malonda, Franklin Vinsentius (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Background: Chronic complications of diabetes mellitus have a significant role in increased morbidity, mortality, disability, and health cost as the population increases every year. Promotive and preventive actions are needed to decrease the prevalence of peripheral diabetic neuropathy. The screening tool for peripheral diabetic neuropathy is Michigan Neuropathy Screening Instrument (MNSI), which consists questionnaire and physical examination.Objective: The purpose of this study was to understand the association of the duration of type 2 diabetes mellitus with the prevalence of peripheral diabetic neuropathy in the Outpatient Unit of Gotong Royong Hospital Surabaya. Method: A cross-sectional study was done using 50 patients in the Outpatient Unit of Gotong Royong Hospital Surabaya. The sampling technique used consecutive sampling with filling out the Michigan Neuropathy Screening Instrument (MNSI) questionnaire. The score of the MNSI questionnaire is analyzed using Chi-Square Test.Result: Among 50 subjects who participated in the study, most were women (78%). The prevalence of patients with peripheral diabetic neuropathy was 28% from all subjects. This chronic complication is divided into two groups based on the duration of diabetes mellitus type 2 with the prevalence of peripheral diabetic neuropathy with a duration of diabetes <5 years (18,2%) and peripheral diabetic neuropathy with the duration of diabetes more than equal to five years old (35,7%). From the analysis with Chi-Square, we did not find a significant association between the duration of type 2 diabetes mellitus and peripheral diabetic neuropathy (p = 0.004).Conclusion: There was no statistically significant association between the duration of type 2 diabetes mellitus and the prevalence of peripheral diabetic neuropathy.